PHP 5 for Dummies - Valade, Janet (Wiley Publishing, 2011)
Think of this book as a friendly introduction to programming in PHP. This book is both an introduction to programming and an introduction to PHP. The book starts with the basics of PHP, including how to tell whether you need to install it. (Full installation instructions are included in Appendix A.) The book describes the basic features of PHP with examples of their use. If you have experience with programming, you can probably just skim this section, but if you don’t, all the programming basics are here.